New murine models of aggressive lymphoma. Issue 4 (20th March 2020) - Flümann, Ruth; Nieper, Pascal; Reinhardt, Hans Christian; Knittel, Gero
Abstract: Diffuse large B cell lymphoma (DLBCL) is the most common type of aggressive lymphoma and has traditionally been subdivided into germinal center B cell-like and activated B cell-like DLBCL, using transcriptome profiling. The recent characterization of the genomic landscape of DLBCL revealed the identity of at least five molecularly-defined subclusters of DLBCL. Intriguingly, these different clusters display a different response to frontline, anthracycline-based chemo-immune therapy. Moreover, multiple, potentially actionable genomic aberrations have been identified in these clusters, including EZH2, CREBBP/EP300, and KMT2D mutations, BCL2 overexpression, PTEN inactivation, CD274 rearrangements and others. With this genomic understanding, it is possible to develop autochthonous mouse models, which capture this genomic complexity. These models can serve as pre-clinical platforms to devise molecularly targeted therapeutic intervention strategies. Here, we review the available mouse models of aggressive lymphoma and indicate which compound-mutant mice may be desirable tools to further advance the field of translational lymphoma research.